2019
DOI: 10.1177/0954406218815716
|View full text |Cite
|
Sign up to set email alerts
|

A novel stability prediction method for milling operations using the holistic-interpolation scheme

Abstract: Currently, accurate and efficient determination of chatter-free cutting conditions is becoming increasingly important. This paper proposes a semi-analytical stability prediction method for milling processes using the holistic-interpolation scheme. The dynamics considering regeneration effect for milling operations is formulated as delay differential equations with time-periodic coefficients. The period of milling dynamic system is divided into two time periods according to the value of the coefficient matrix. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 51 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…It was shown that the method had higher convergence rate and computation accuracy, validated by comparisons with the semi-discretization method [26]. More recently the so-called semi-analytical holistic interpolation method (HIM) with both high efficiency and accuracy was proposed by Cheng jin and co-worker to predict stability of milling processes which reduce more computational time than Update Full Discretization Method (UFDM) [27].…”
Section: Introductionmentioning
confidence: 96%
“…It was shown that the method had higher convergence rate and computation accuracy, validated by comparisons with the semi-discretization method [26]. More recently the so-called semi-analytical holistic interpolation method (HIM) with both high efficiency and accuracy was proposed by Cheng jin and co-worker to predict stability of milling processes which reduce more computational time than Update Full Discretization Method (UFDM) [27].…”
Section: Introductionmentioning
confidence: 96%
“…The discretization method has been widely investigated and applied as an interesting and efficient time domain method [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. By equally discretizing the time period and approximating the delayed term with different polynomials, the zeroth-order and first-order semi-discretization methods ( ZSDM and FSDM ) were proposed by Insperger and Stepan, respectively [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the state, delayed, and periodic coefficient terms were approximated by the holistic-interpolation method in Ref. [18]. Subsequently, third-order [19][20][21][22] and higher-order [23][24][25] FDMs were proposed to increase the precision of the stability prediction.…”
Section: Introductionmentioning
confidence: 99%
“…The test rig is detailed introduced in the post paper (Wang and Shi, 2021). High accuracy milling machine improves the quality of the test rig (Qin, et al, 2018(Qin, et al, , 2019. Figure 3 shows the main mechanism of the test rig and the schematic of the measurement system.…”
Section: Introduction Of Test Rigmentioning
confidence: 99%